Aflatoxins: Climate change and biodegradation. (October 2015) - Baranyi, Nikolett; Kocsubé, Sándor; Varga, János
Highlights: Aflatoxins are among the economically most important mycotoxins produced by Aspergilli. Aflatoxin B1 exhibits hepatocarcinogenic and hepatotoxic properties. Climate change led to the presence of aflatoxin producing species in areas where they were not present previously. Minimalization of health risk that aflatoxins pose could be either by the prevention of contamination of foods and feeds, or by the biodegradation of aflatoxins. Abstract : Aflatoxins are the most important mycotoxins produced predominantly by certain strains whithin species of the Aspergillus genus. Aflatoxin contamination of foods and feeds causes serious economic and health problem worldwide. Aflatoxin B1 exhibits hepatocarcinogenic and hepatotoxic properties, and it is the most potent naturally occurring carcinogen. Climate change has led to the presence of aflatoxin producing species, especially A. flavus and consequently aflatoxin contamination, in areas where they were not prevalent previously. In this review, an overview of recent progress on aflatoxin research including producing fungi, occurrence, and potential biodegradation methods is provided.